Game accessibility course design modules in higher education - Westin, Thomas (Frontiers in Computer Science, 2024)
Game accessibility has evolved significantly during the last ten years, both within the industry and in research. Further inclusion in both games and the game industry requires educational resources useful within game curricula, which has been developed by the industry, to raise awareness about design and development regarding game accessibility and related issues. The purpose of this paper is to explain how inclusive game design and game accessibility can be taught to students in higher education, for curricular design, in-between generic curricula and practice. A tentative curriculum framework (TCF) was developed by the author and a co-author, based on feedback from peers. The problem is that there is still a gap between the basic structure of the TCF and how to apply it in higher education courses. The goal with this paper is to exemplify how this can be done with a set of generalized modules with course activities based on teaching by the author for two decades, that can be implemented in higher education courses, either modified or as-is, related to the TCF. A set of example modules consisting of activities is presented that can be adapted and applied by peer educators. Future work involves transforming the modules themselves into open educational resources, organized based on the TCF. Hopefully, this can motivate peer educators to also contribute with further open educational resources in a common repository, to aid each other as a community of educators developing best practices for teaching about game accessibility in higher education.